Trastorno disocial y las conductas autodestructivas en los adolescentes 10mo año de educación básica de la Unidad Educativa 13 de Abril año 2019 - Cabrera Moreira, Genesis Juliana (2019)
Disocial disorder is defined as a behavioral disorder that is, the recurrent presence of distorted, destructive and negative behaviors or behaviors, in addition to transgressors of social norms in the individual's behavior, said disorder is classified into three phases: Disorder Disocial limited to the Family Context, Disocial Disorder in non-socialized children Disocial Disorder in socialized children. On the other hand, self-destructive behaviors, is an action that the individual performs to put his life at risk. The self-destructive behaviors can be direct and indirect, but in this project we are going to focus on the indirect ones since they are actions that contemplate death as a consciously unwanted effect, these are small risks, selfcasting behaviors that, when done constantly, are transformed into A form of slow death. The main objective of this research project is to establish the main consequences of dissociative disorder and the self-destructive behaviors of adolescents in the 10th year of basic education of the educational unit April 13. As a proposal there will be the realization of psychoeducational techniques for the better management of disocial disorder and self-destructive behaviors in adolescents of the 10th year of basic education of the educational unit April 13, will have as scope to achieve greater awareness of parents and teachers before the risks that the adolescent can suffer when manifesting said conduct or disorder